SEASONAL DENSITY OF ANOPHELES CULICIFACIES AND AN. SUBPICTUS (DIPTERA: CULICIDAE) IN RELATION TO CERTAIN ABIOTIC FACTORS - SRIVASTAVA, NISHA; JAUHARI, RAKESH KUMAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1992)
Studies on the seasonal density of Anopheles culicifacies and An. subpictus were carried out from January to December, 1990 in eight villages of Sahaspur area in Doon Valley, showing a single peak of high prevalence i.e. July to September. Man hour densities of Anophelines varied from 0.84 to 28.1 during the study period. Monthly changes in larval density were recorded and the highest density observed in August 1990. Low rainfall, drought and suitable temperature affected densities of mosquitoes. It was also noted that the villages which are situated on the bank of river are more prone to malaria incidence because of high mosquitogenic conditions.